The Implementation of Ibn al-Haytham’s Method for Determining Qibla Direction Using Raspberry Pi - Sanjaya, W. S. Mada; Roziqin, Akhmad; Anggraeni, Dyah; Mamat, Mustafa (Universitas Muhammadiyah Malang, 2022)
Ibn al-Haytham or better known as Alhazen (965-1040 AD) was a great Muslim scientist who mastered many disciplines. One of his works entitled